Migration and dispersal patterns of bats and their influence on genetic structure. (11th October 2012) - Moussy, Caroline; Hosken, D.J.; Mathews, F.; Smith, G.C.; Aegerter, J.N.; Bearhop, S.
Abstract Bats are important ecosystems service providers, make a significant contribution to biodiversity and can be important pests and disease vectors. In spite of this, information on their migration and dispersal patterns is limited. In temperate bats, migration is most evident in females. This reflects seasonal differences in their habitat requirements, and the fact that seasonally suitable sites can be geographically distant. Tropical bats mainly migrate to track variation in food availability. Little direct information is available on the patterns and drivers of bat dispersal, although drivers may include mate competition and inbreeding avoidance. In many temperate species, differential energy requirements and local resource competition among the sexes drive sexual segregation in the summer: females remain philopatric to their natal region, and frequently to their natal colony, while males disperse. In contrast, many tropical Pteropodidae form single‐male/multi‐female groups in which local resource defence contributes to female‐biased or all‐offspring dispersal from the natal site. Population genetic studies are the most common source of evidence used to infer the spatial dynamics of bats. As expected, migratory species tend to have less genetically structured populations over large geographical scales due to mating outside of breeding areas, weak migratory connectivity and long‐distance movements. In contrast and as expected, populations of sedentary species tend to be more differentiated at smaller geographical scales. Despite this general pattern, a range of factors, including historical events, dispersal capabilities, and behavioural, ecological and geographical barriers, are implicated in the genetic partitioning of bat populations, irrespective of movement patterns. These factors limit the study of bat movements using only genetic methods. Combining population genetics with other methods, such as mark–recapture, tracking or stable isotope analysis, should provide more insight into the movements of these ecologically and economically important species.